Pengaruh Loyalitas Kepengurusan, Kelanjutan Kepengurusan Serta Norma Organisasi Pada Hasil Kerja Kepengurusan (Studi pada Kepengurusan BEM FEB UNISMA 2022) - Ro’is Ro’is; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This studies are aiming to be determining for decising for moments of progressive business development that have changed since a long time ago to become more intimate, corporations in the new world seem to be dealing with progressive humanity, so that it will create an increasingly sustainable stigma. That way corporations should be able to create an innovation that can be used as a differentiator from other companies, besides that companies must be able to treat existence and develop work results in all fields. So with this activity. BEM FEB 2022 using industry, bank loans and investments is considered to be a big problem to be mobilized in other fields so as to increase funds for corporations. With the high activity of the community during the pandemic, it caused changes in all aspects of life that were not spared from technological developments, such as online marketing on the performance of the management on the management of BEM FEB 2022. The results of the determination test show a proportion of 70.8%, where the performance of the management can be influenced by affective commitment, continuance commitment and normative commitment. It is suggested to further researchers that they are expected to be able to examine the performance of the Management using another methodology due to the possibility of bias towards the respondents' answers in the questionnaire.Keywords: Management Performance, Affective Commitment, Continuance Commitment, Normative Commitment